The influence of pyrolysis and matrix modifiers on determination of Cr and Pb in sediment samples by GFAAS - Risfidian Mohadi; José A.C. Broekaert (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: The Influence of pyrolysis and matrix modifiers on determination of Cr and Pb in sediment samples using graphite furnace atomic absorption spectrometry has been investigated. The sediment samples including three certified reference materials (CRMs) are reported. Analyses were performed using microwave assisted dissolution. The matrix modifiers Mg(NO3)2, Pd+Mg(NO3)2 and NH4H2PO4were shown to be optimazed. The recovery for Cr and Pb in CRMs in the case of sample dissolution was found to be between 81 to 91% for Cr and 94 to 98% for Pb of the certified values, respectively.Keywords: Sediment, Pyrolysis, Matrix modifiers, Cr, PbAbstrak (Indonesia): Pengaruh pirolisis dan matriks pengubah pada penentuan Cr dan Pb dalam sampel sedimen menggunakan tungku grafit spektroskopi serapan atom telah diteliti. Sampel sedimen termasuk tiga bahan referensi bersertifikat (CRMs) dilaporkan dianalisis dengan menggunakan bantuan microwave ekstraktor. Matriks pengubah Mg(NO3)2, Pd+Mg(NO3)2 dan NH4H2PO4 telah digunakan dan menghasilkan nilai temu balik untuk Cr dan Pb dalam CRMs ditemukan antara 81-91% untuk Cr dan 94-98 % untuk Pb dari nilai sertifikat masing-masing.Katakunci: Sedimen, Pirolisis, Matrix modifiers, Cr, Pb